The FGF/FGFR/c-Myc axis as a promising therapeutic target in multiple myeloma - Arianna Giacomini; Sara Taranto; Giorgia Gazzaroli; Jessica Faletti; Davide Capoferri; Raffaella Marcheselli; Margherita Sciumè; Marco Presta; Antonio Sacco; Aldo M. Roccaro (Journal of Experimental & Clinical Cancer Research)
Abstract Among blood cancers, multiple myeloma (MM) represents the second most common neoplasm and is characterized by the accumulation and proliferation of monoclonal plasma cells within the bone marrow. Despite the last few decades being characterized by the development of different therapeutic strategies against MM, at present such disease is still considered incurable. Although MM is highly heterogeneous in terms of genetic and molecular subtypes, about 67% of MM cases are associated with abnormal activity of the transcription factor c-Myc, which has so far revealed a protein extremely difficult to target. We have recently demonstrated that activation of fibroblast growth factor (FGF) signaling protects MM cells from oxidative stress-induced apoptosis by stabilizing the oncoprotein c-Myc. Accordingly, secretion of FGF ligands and autocrine activation of FGF receptors (FGFR) is observed in MM cells and FGFR3 genomic alterations represent some 15–20% MM cases and are associated with poor outcome. Thus, FGF/FGFR blockade may represent a promising strategy to indirectly target c-Myc in MM. On this basis, the present review aims at providing an overview of recently explored connections between the FGF/FGFR system and c-Myc oncoprotein, sustaining the therapeutic potential of targeting the FGF/FGFR/c-Myc axis in MM by using inhibitors targeting FGF ligands or FGF receptors. Importantly, the provided findings may represent the rationale for using FDA approved FGFR TK inhibitors (i.e. Pemigatinib, Futibatinib, Erdafitinib) for the treatment of MM patients presenting with an aberrant activation of this axis.